A contribution to the physicochemical characterization of Eugenia involucrata DC. fruits to estimate genetic variability - Mayer, Leonardo; Nienow, Alexandre Augusto; Tres, Laura; Trevizan Chiomento, José Luís (Comunicata Scientiae, 2022)
Brazil has one of the greatest diversities in native fruit trees, but many species, despite the great environmental and economic potential for small farms, are little studied, such as the cherry-of-the-rio-grande (Eugenia involucrata DC.). The hypothesis of this research was that there is a high genetic diversity due to the propagation by seeds, occurring genotypes that produce better quality fruits which can be used to implement genetic improvement programs and the production of seedlings with better productive performance. So, this study aimed to characterize fruits of this species' genotypes and to evaluate the genetic divergence applying multivariate analysis techniques. Genotypes of different ages found in rural and urban areas of the municipality of Serafina Corrêa, Rio Grande do Sul, were evaluated, with 50 genotypes in 2018 and 38 genotypes in 2019, since twelve did not bear fruit. Data were submitted to determine the mean and standard deviation. To assess genetic diversity, the relative contribution of characters was determined by the Singh method; the average Euclidean distance standardized matrix (UPGMA) and dendrograms were generated; and Tocher's optimization method was applied. Results showed that UPGMA and Tocher clustering methods are more efficient in representing the diversity between genotypes. Fruits characteristics varied from one year to another, due to the combination of biotic and abiotic factors (water regime), resulting in changes of characters with greater contribution in the divergence and formation of similar groups. The content of total soluble solids (TSS) in 2018 and fruit mass in 2019 harvest were characters that most contributed to the genetic divergence. It was concluded that the physicochemical characters of fruits revealed the existence of genetic divergence among genotypes, allowing the selection of agronomically superior plants.